(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2017)
Introduction: HELLP syndrome is a variant of pre-eclampsia with severe features that presents with haemolysis, elevated liver enzymes and low platelets. It is associated with significant morbidity and mortality. Case presentation: A 24 year old Para 3+0 Gravida 4 at term with prolonged labour and severe pre-eclampsia presented from a peripheral facility without a referral letter. She delivered before arrival and had one convulsion prior to admission. Magnesium sulphate and antihypertensives were initiated at admission. A few hours later, she convulsed two more times, her level of consciousness deteriorated; she developed a bleeding diathesis and went into renal shutdown. At this point, magnesium sulphate was stopped in favour of phenytoin. Steroids were administered and acute haemodialysis was performed. Her neurological status and renal function improved and the HELLP syndrome resolved over the next five days. She was observed for three more days and was discharged in good condition, with no adverse sequelae noted during follow up. Result: Prompt diagnosis and timely conscientious treatment were the keys to the good outcome in this patient. Conclusion: A high index of suspicion of HELLP syndrome is essential in all patients with hypertensive disorders of pregnancy in order to enable early diagnosis and prompt management.